(x² + 6x)2 + 8 (x2 + 6x) = 9;​

FeliceMell FeliceMell    3   05.04.2021 11:01    0

Ответы
prencessviki prencessviki  05.05.2021 11:04
ответ :
x₁ = -3
x₂ = -3 - √10
x₃ = -3 +√10

(x² + 6x)² + 8(x² + 6x) = 9

t = x² + 6x

t² + 8t = 9
t² + 8t - 9 = 0

{ t₁ + t₂ = -8
{ t₁ × t₂ = -9

t₁ = -9
t₂ = 1

x² + 6x = -9
x² + 6x + 9 = 0

Решаю методом выделения полного квадрата :

(x + 3)² = 0
x + 3 = 0
x₁ = -3

x² + 6x = 1
x² + 6x - 1 = 0

Решаю тем же методом, что и уравнение :

(x + 3)² - 10 = 0
(x + 3)² = 10

x₂ = -3 - √10
x₃ = -3 + √10
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра